2014
DOI: 10.1371/journal.pone.0098740
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of WHO Transmitted Drug Resistance Mutations by Deep Sequencing in Antiretroviral-Naïve Subjects in Hunan Province, China

Abstract: BackgroundThere are few data on the prevalence of WHO transmitted drug resistance mutations (TDRs) that could affect treatment responses to first line antiretroviral therapy (ART) in Hunan Province, China.ObjectiveDetermine the prevalence of WHO NRTI/NNRTI/PI TDRs in ART-naïve subjects in Hunan Province by deep sequencing.MethodsART-naïve subjects diagnosed in Hunan between 2010–2011 were evaluated by deep sequencing for low-frequency HIV variants possessing WHO TDRs to 1% levels. Mutations were scored using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…Early antiviral treatment can control virus replication as early as possible, and reduce the possibility of drug resistance [13,18]. The result showed that CRF01 AE is still the most dominance subtype in Hunan province (64.14%), followed by subtype BC,B and C, the finding corresponding to the last years of the Hunan Province molecular epidemiology survey (2009-2015) results [10][11][12]19].. The prevalence of HIV-1 subtype B was significantly higher in Zhangjiajie City compared with other areas in Hunan province.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Early antiviral treatment can control virus replication as early as possible, and reduce the possibility of drug resistance [13,18]. The result showed that CRF01 AE is still the most dominance subtype in Hunan province (64.14%), followed by subtype BC,B and C, the finding corresponding to the last years of the Hunan Province molecular epidemiology survey (2009-2015) results [10][11][12]19].. The prevalence of HIV-1 subtype B was significantly higher in Zhangjiajie City compared with other areas in Hunan province.…”
Section: Discussionmentioning
confidence: 97%
“…The Chinese national free ARV treatment policy guidelines recommend that patients on ART should have an HIV viral load test at least once a year [10][11][12]. If the viral load is > 1000 copies/ml, a HIV drug resistance genotypic test (Sanger Sequencing based) should be performed.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more HIV-infected MSM have received the free antiretroviral treatment. 29 Another recent study has reported that RT-related TDRs were detected among MSM in Kunming. 30 Several drugs have low genetic bottleneck, and one point mutation can make HIV resistant to NNRTIs.…”
Section: Discussionmentioning
confidence: 97%
“…22,28,29 The increasing trend of TDR in some regions of China deserves the concern from public health departments and medical workers. 22,28,29 The increasing trend of TDR in some regions of China deserves the concern from public health departments and medical workers.…”
Section: Discussionmentioning
confidence: 99%